Growth vs. fixed mindset : the relationship between student's mindset, resilience and psychological well-being - Silja Gunnarsdóttir 1999- (2021)
The purpose of this study was to examine students’ mindset, along with their psychological well-being and resilience. Prior research has revealed that young individuals, who had a more growth-oriented mindset, showed less prominent mental health issues than their peers as well as higher resilience. This study hypothesized that participants with a more growth-oriented mindset would score higher on the psychological well-being scale, as well as the resilience scale. To test these hypotheses, a questionnaire was submitted to students attending a university in Iceland. Participants were 130 in total - 38 men and 92 women - and 88.5% of them were between the ages of 18 – 34. Findings suggest that a moderate negative correlation was present between the students’ mindset, psychological well-being and resilience. Participants with a growth-oriented mindset scored, on average, higher on the psychological well-being scale, as well as the resilience scale. This confirms previous research regarding mindset, psychological well-being and resilience. In conclusion, both of the hypotheses could be confirmed. However, some limitations were present in this study and further research on mindset is required. Key words: growth mindset, fixed mindset, psychological well-being, resilience, mindset Markmið rannsóknarinnar var að kanna tengsl hugarfars nemenda við andlega vellíðan og þrautseigju. Rannsóknir sýna að einstaklingar með vaxtar hugarfar eru líklegri til að upplifa meiri andlega vellíðan, samanborið við einstaklinga með festu hugarfar. Ennfremur hafa rannsóknir sýnt að einstaklingar með vaxtar hugarfar eru líklegri til að búa yfir meiri þrausteigju en einstaklingar með festu hugarfar. Tvær tilgátur eru settar fram í þessari rannsókn. Fyrri tilgátan segir að þátttakendur rannsóknarinnar sem sýna vaxtar hugarfar séu líklegri til að sýna fram á meiri andlega vellíðan en þeir sem sýna festu hugarfar. Síðari tilgátan segir að þátttakendur rannsóknarinnar sem sýna vaxtar hugarfar séu líklegri til að búa yfir meiri þrautseigju, ...